(untitled) (Marketing Journal, 2025)
This article explores the theoretical and methodological foundations influencing the development of international franchises. It analyzes the global evolution of the franchise business model, as well as economic, legal, and cultural factors. Methodological approaches are reviewed, and the success factors and challenges of international franchising are identified. The study discusses future development directions and provides practical recommendations for companies planning to expand franchise systems in int ernational markets.